Reuse of Clay Brick Waste in Mortar and Concrete - Lihua Zhu; Zengmei Zhu (Advances in Materials Science and Engineering)
The application of recycled clay brick can not only solve the disposal problem of demolished solid waste but also reduce ecological environment damage caused by the excessive development of resources. Clay brick powder (CBP) exhibits pozzolanic activity and can be used as cement replacement. Recycled clay brick aggregate (RBA) can be used to substitute natural coarse aggregate. Recycled clay brick aggregate concrete (RBAC) can attain suitable strength and be used in the production of medium- and low-strength concrete. Clay brick waste as potential partial cement and aggregate replacement material is reviewed herein. Performances in terms of mechanical and durability-related properties of mortar and concrete are discussed. Understanding the properties of clay bricks is crucial to further research and applications.